2005
DOI: 10.1177/154193120504900211
|View full text |Cite
|
Sign up to set email alerts
|

Age Differences in Search Time for Two Over-Thecounter (OTC) Drug Label Formats

Abstract: This study compared older and younger adults' knowledge acquisition and search times for information on older and newer over-the-counter (OTC) drug label formats. The results showed that younger adults were faster than older adults. The younger group performed significantly faster with the newer formatted labels than the older formatted labels, whereas the older adults yielded no difference between the two formats. Potential directions for future research are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Older adults have been identified as an important group for study with respect to OTC use as they represent a growing segment of the population and are heavy users of OTC (and prescription) products [38,44]. One study found that younger consumers processed label information faster than older consumers, although label comprehension did not differ across groups and was relatively high overall [45]. Importantly, as a group, older adults (age 65 and up) exhibit lower levels of health literacy than younger age groups [44] which, as discussed above, inhibits understanding of and compliance with DFL instructions [46].…”
Section: Individual-level Factors and The Dflmentioning
confidence: 99%
“…Older adults have been identified as an important group for study with respect to OTC use as they represent a growing segment of the population and are heavy users of OTC (and prescription) products [38,44]. One study found that younger consumers processed label information faster than older consumers, although label comprehension did not differ across groups and was relatively high overall [45]. Importantly, as a group, older adults (age 65 and up) exhibit lower levels of health literacy than younger age groups [44] which, as discussed above, inhibits understanding of and compliance with DFL instructions [46].…”
Section: Individual-level Factors and The Dflmentioning
confidence: 99%
“…Thus, standardization has the potential to meet consumer OTC medicine information needs and improve OTC label quality, as demonstrated by previous testing of the U.S. Drug Facts label format 20 and in particular for younger consumers. 21,22 Despite promising evidence for standardization, conveying information using the Drug Facts label format does not completely safeguard against consumer misunderstanding of critical OTC medicine information. 36 Consequently, it is imperative to involve consumers in refining and testing the MIB (whose format was based on the Drug Facts label 25 ) in preparation for implementation, as seen by the breadth of suggested improvements.…”
Section: Discussionmentioning
confidence: 99%
“…Different regulatory environments have explored various strategies to improve OTC labelling quality for consumers, such as the recommendation for 'user testing' in OTC label development and testing as part of the Labelling Code of Practice in Australia, 19 and the standardization of OTC labels in the United States (U.S.) with the Drug Facts label format. 20 Two large-scale studies, that explored consumer preferences and testing of the Drug Facts label format versus older OTC labels, supported the legislation of OTC label standardization in the U.S. 20 The Drug Facts label format appeared to improve the time taken for consumers to locate information [20][21][22] in comparison with older OTC labels.…”
Section: Introductionmentioning
confidence: 99%